Clinical forms of chikungunya in Gabon, 2010. - Dieudonné Nkoghe; Roland Fabrice Kassa; Mélanie Caron; Gilda Grard; Illich Mombo; Branly Bikié; Christophe Paupy; Pierre Becquart; Ulrich Bisvigou; Eric Maurice Leroy (Public Library of Science (PLoS), 2012)
BACKGROUND: Chikungunya virus (CHIKV) has caused multiple outbreaks in tropical and temperate areas worldwide, but the clinical and biological features of this disease are poorly described, particularly in Africa. We report a prospective study of clinical and biological features during an outbreak that occurred in Franceville, Gabon in 2010. METHODOLOGY/PRINCIPAL FINDINGS: We collected, in suspect cases (individuals presenting with at least one of the following symptoms or signs: fever, arthralgias, myalgias, headaches, rash, fatigue, nausea, vomiting, diarrhea, bleeding, or jaundice), blood samples, demographic and clinical characteristics and outcome. Hematological and biochemical tests, blood smears for malaria parasites and quantitative PCR for CHIKV then dengue virus were performed. CHIKV+ patients with concomitant malaria and/or dengue were excluded from the study. From May to July 2010, data on 270 laboratory-confirmed CHIK patients were recorded. Fever and arthralgias were reported by respectively 85% and 90% of patients, while myalgias, rash and hemorrhage were noted in 73%, 42% and 2% of patients. The patients were grouped into 4 clinical categories depending on the existence of fever and/or joint pain. On this basis, mixed forms accounted for 78.5% of cases, arthralgic forms 12.6%, febrile forms 6.7% and unusual forms (without fever and arthralgias) 2.2%. No cases of organ failure or death were reported. Elevated liver enzyme and creatinine levels, anemia and lymphocytopenia were the predominant biological abnormalities, and lymphocytopenia was more severe in patients with high viral loads (p = 0.01). CONCLUSIONS/SIGNIFICANCE: During CHIK epidemics, some patients may not have classical symptoms. The existence of unusual forms and the absence of severe forms of CHIK call for surveillance to detect any change in pathogenicity.